2021
DOI: 10.1155/2021/8714873
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Interventions for Hispanic Women in the United States: A Systematic Review

Abstract: Background. Obesity rates in Hispanic women residing in the United States (U.S.) are disproportionately high, increasing the risk of obesity-related disease and mortality. The effectiveness of interventions targeting weight loss in this population remains largely unknown. Purpose. The purpose of this review was to systematically evaluate the evidence related to the effectiveness of weight loss interventions conducted among U.S. Hispanic women and provide guidance for future research. Methods. Bibliographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(330 reference statements)
0
6
0
Order By: Relevance
“…Several previous systematic reviews have considered the relationship between characteristics where inequalities may occur and interventions for overweight or obesity. 9 , 10 , 11 , 12 , 13 , 14 The United States Preventive Services Taskforce (USPSTF) considered the overall effectiveness of behavioral and pharmacological interventions for overweight and obesity 3 and provided narrative comment about some aspects of inequality. The authors found that unless the intervention was targeted towards a specific ethnicity, ethnicity and SES were frequently not reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous systematic reviews have considered the relationship between characteristics where inequalities may occur and interventions for overweight or obesity. 9 , 10 , 11 , 12 , 13 , 14 The United States Preventive Services Taskforce (USPSTF) considered the overall effectiveness of behavioral and pharmacological interventions for overweight and obesity 3 and provided narrative comment about some aspects of inequality. The authors found that unless the intervention was targeted towards a specific ethnicity, ethnicity and SES were frequently not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Seven reviews focused on race or ethnicity. 9 , 10 , 11 , 12 , 13 , 14 , 15 Two only included interventions that were targeted towards Latinos in America, 9 , 14 and one only included interventions that were tailored towards African American women. 10 Four systematic reviews included studies if they reported more than one race or ethnicity represented in their sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mediterranean diet has been found to be among the most effective diets to improve cardio-metabolic factors associated with NAFLD and to induce weight loss [71], the most effective way to reduce hepatic steatosis and improve histopathological features of NASH [11]. However, barriers to engage in such dietary modifications and long-term weight loss maintenance have been difficult among Hispanic patients for a variety of reasons [30,72]. First, the cultural relevance and overall acceptability of the Mediterranean diet among Hispanics may be questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding feasibility and acceptability, our mHealth intervention was well received and produced a retention rate of 88.9%. In general, weight loss interventions in Hispanic adults have previously reported lower retention rates; however, they did not include mHealth components [ 40 ]. Rosas et al [ 14 ] observed a retention rate of 96.9%, suggesting that technology-mediated strategies may support retention efforts [ 14 ].…”
Section: Discussionmentioning
confidence: 99%